Salustijeva razlaga za izvor državljanskih vojn v zadnjih desetletjih republike - Maver, Aleš (Clotho, 2022)
The article’s starting point is the assumption that much of Sallust’s historiographical work is overshadowed by the experience of a prolonged civil war in Rome during his lifetime. This is visible in the historian’s presentation of the nobility’s brutal crushing of the Gracchi and his portrayal of Sulla’s rule as the source of the extensive moral chaos in the decades after his conquest of Rome. In analyzing the causes of the crisis of the Roman republic in the 60s BC and at the time of his writing, Sallust arguably tried to present himself as a non-partisan observer, at times stressing the faults of political leaders of both conflicting camps, the nobility, and the plebs. Nevertheless, Sallust certainly did not share Cicero’s view that the concord of both main ruling class groups could be a good remedy for Rome’s problems. Instead, he took the social roots of the crisis much more seriously. In doing so, he undoubtedly blamed the ruling class for the crisis. Hence, even declarations of ambiguous heralds of change like Catiline deserved attention in Sallust’s view. On the one hand, the historian affirmed Cicero’s excruciating depiction of the conspiracy’s leader and even portrayed him as a demagogue who emphasized his patrician origins. On the other hand, he depictsed his reasoning about the situation in Rome as trustworthy, particularly regarding his ardent invective against the nobles.
Keywords: Catiline; civil wars of the Roman Republic; državljanske vojne v času rimske republike; Katilina; rimska aristokracija; rimski senat; Roman nobility; Sallust; Salustij; Sula; Sulla; the Roman senate